1999
DOI: 10.1002/(sici)1097-0010(199908)79:11<1461::aid-jsfa388>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Identification of impact odorants of young red wines made with Merlot, Cabernet Sauvignon and Grenache grape varieties: a comparative study

Abstract: An Aroma Extract Dilution Analysis (AEDA) has been carried out on three monovarietal young red wines plus a mixture of wines aged one year. The aromograms contain 85 odour‐active regions classified in four categories of intensity. The 11 most powerful odorants, 14 out of the 17 second‐most powerful, and 34 of the rest could be identified using a HPLC prefractionation method and standard HRGC‐MS‐olfactometric techniques. The most active odorants of the monovarietal wines were isoamyl and β‐phenylethyl alcohols,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
113
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 159 publications
(122 citation statements)
references
References 17 publications
6
113
0
1
Order By: Relevance
“…The origins of wine aroma and bouquet (here referred to collectively as aroma) have been of major interest over the last century, with advances made through the development and use of modern analytical techniques coupled to hybrid analytical/sensory methods (Guth 1997b, López et al 1999, Francis and Newton 2005, Polášková et al 2008, Ebeler and Thorngate 2009) and through multivariate statistical comparisons with descriptive sensory analysis (Noble and Ebeler 2002, Lee and Noble 2003, 2006, Escudero et al 2007, Sáenz-Navajas et al 2010. The combination of analytical and sensory methodologies has been particularly important in resolving effects of interactions of aroma compounds with the nonvolatile matrix (Pineau et al 2007, Robinson et al 2009, Sáenz-Navajas et al 2010) as well as with other volatile compounds (Atanasova et al 2005, Escudero et al 2007, Pineau et al 2009).…”
Section: Origins Of Wine Aromamentioning
confidence: 99%
“…The origins of wine aroma and bouquet (here referred to collectively as aroma) have been of major interest over the last century, with advances made through the development and use of modern analytical techniques coupled to hybrid analytical/sensory methods (Guth 1997b, López et al 1999, Francis and Newton 2005, Polášková et al 2008, Ebeler and Thorngate 2009) and through multivariate statistical comparisons with descriptive sensory analysis (Noble and Ebeler 2002, Lee and Noble 2003, 2006, Escudero et al 2007, Sáenz-Navajas et al 2010. The combination of analytical and sensory methodologies has been particularly important in resolving effects of interactions of aroma compounds with the nonvolatile matrix (Pineau et al 2007, Robinson et al 2009, Sáenz-Navajas et al 2010) as well as with other volatile compounds (Atanasova et al 2005, Escudero et al 2007, Pineau et al 2009).…”
Section: Origins Of Wine Aromamentioning
confidence: 99%
“…The most active odorants of these three varietal young red wines suggested by aroma extract dilution analysis (AEDA) were isopentyl and β-phenylethyl alcohols, the ethyl esters of butyric, isobutyric, 2-methyl butyric and hexanoic acids, γ-nonalactone and eugenol. Data showed that differences between these varieties are quantitative rather than qualitative [7,8]. In past decades, the unique characteristics of Chinese wine began to attract notice with the rapid development of wine production in China.…”
Section: Introductionmentioning
confidence: 99%
“…The Riesling varieties are highly 'terroir-expressive' , meaning that the character of Riesling wines is clearly influenced by the wine's place of origin. The amount of 3,7-dimethyl-1,6-octadien-3-ol ranged from 0.79 to 1.16 mg/l, which fully corresponds to the character of grape varieties (López et al 1999;Guarrera et al 2005). It is evident from the results of the wine aroma analysis that the applied process of vinification ensures acceptable quality of sparkling wine.…”
Section: Resultsmentioning
confidence: 89%